Poverty dynamics in Brazilian metropolitan areas: An analysis based on Hulme and Shepherd's categorization (2002–2011) - Solange Ledi Gonçalves; Ana Flávia Machado (EconomiA, 2015)
Ever-more sophisticated studies on the methodological approach and the conceptual scope of poverty have led to a consensus among scholars on the dynamic characteristic of this phenomenon – in other words, the existence of an in-and-out of privation movement of individuals and families. Within this context, Hulme and Shepherd (2003) defined five groups according to the location of the punctual and average indicators of poverty vis-à-vis the poverty line. This paper's objective is to adapt this typology to Brazil, using PME (Monthly Job Survey) micro-data for the 2002–2011 timeframe and the six Brazilian Metropolitan Regions covered by PME as well as, by estimating a multinomial logit, investigate which family characteristics relate to a greater or lesser chance of belonging to each of the chronic and transitory poverty categories. Categorization allows observation that, despite a sweeping across-the-board decline in the percentage of families in all poverty categories in the past decade, those families always or usually poor display demographic, socioeconomic, access to and insertion into the labor market categories which differ from families in transitory poverty or classified as never poor. Moreover, Northeastern metropolitan regions (Salvador and Recife) have higher percentages of chronic or transitory poverty. Multinomial logit estimates make it possible to verify that families whose members have completed secondary schooling or college or hold a higher-qualified occupation stand lesser chances of entering into or remaining in poverty. Results call for differentiating among poor families, as they enter into or leave poverty – which is tantamount to saying that the dynamics of poverty must be taken into account as public policies are drawn up.